Investigating factor that affect awareness on retirement planning / Mohamad Ibrahim Mohamad Shah and Muhammad Amirul Asraff Abd Wahab - Mohamad Shah, Mohamad Ibrahim; Abd Wahab, Muhammad Amirul Asraff (Faculty of Business and Management, 2013)
The main purpose of this study is to investigate the comportment of PETRONAS Group in awareness on retirement planning. This topic was chosen because the researchers want to know severely about the perception and preparation of the employees towards their retirement planning. The factors that involved awareness in retirement planning are knowledge, age factor, level of income, gender and financial education programmes. Primary data of this study is distribution of questionnaire. The aim is to get 300 respondents, so 300 questionnaires were distributed to respondents among the PETRONAS Group. All 300 questionnaires managed to be collected and were analyzed using SPSS Version 19. The Pearson’s Correlation was used to find the significant relationship between those variables. Multiple Regression method was used to find the best benefactor. The findings, only two independent variables manage to have significant result towards dependent variable which is awareness on retirement planning and can be used in making prediction in this study.